2011
DOI: 10.4048/jbc.2011.14.4.322
|View full text |Cite
|
Sign up to set email alerts
|

Does Immediate Breast Reconstruction after Mastectomy affect the Initiation of Adjuvant Chemotherapy?

Abstract: PurposeThe frequency of immediate breast reconstruction (IBR) is increasing, and the types of reconstruction used are diverse. Adjuvant chemotherapy is a life-saving intervention in selected high-risk breast cancer patients. The aim of our study was to determine how IBR and type of reconstruction affect the timing of the initiation of chemotherapy.MethodsWe obtained data from female breast cancer patients treated by mastectomy with IBR (IBR group) and without IBR (mastectomy only group) who received adjuvant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Different cut-off points were chosen: two studies chose 8 weeks, three studies chose 12 weeks, and one study reported the number of patients per 10 days. No statistically significant differences for this comparison were found for these cut-off points [ 7 , 16 , 18 , 20 , 22 , 26 ]. In patients with IBR, the few delays beyond 12 weeks after surgery were not related to the type of surgery, but due to social reasons and delayed diagnostic test results [ 7 , 20 ].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Different cut-off points were chosen: two studies chose 8 weeks, three studies chose 12 weeks, and one study reported the number of patients per 10 days. No statistically significant differences for this comparison were found for these cut-off points [ 7 , 16 , 18 , 20 , 22 , 26 ]. In patients with IBR, the few delays beyond 12 weeks after surgery were not related to the type of surgery, but due to social reasons and delayed diagnostic test results [ 7 , 20 ].…”
Section: Resultsmentioning
confidence: 95%
“…Due to lack of pertinent information, the legitimacy to do a meta-analysis was doubted. Moreover, an I 2 of 98 % was observed, after pooling the studies that used the same definition for time to chemotherapy and reported mean values and standard deviations [ 7 , 17 , 20 , 22 , 23 ], indicating a high statistical heterogeneity. We found no obvious explanation for this high statistical heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Multiple factors, including age, disease-specific characteristics, type of surgical procedure, and additional testing have been found to influence this trend. [21][22][23][24][25][26][27] In an era of increasing use of Oncotype DX to assist with chemotherapy treatment decisions, an aging population with comorbidities needing to be addressed, and the more prevalent use of MIR, it is not surprising that wait times to adjuvant therapy continue to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high risk of developing a subsequent breast cancer (as high as 3% yearly rate in some reports [2]), no survival benefit has been observed with risk-reducing contralateral mastectomy [7], highlighting the need to better select women for this treatment. Risk-reducing surgery, which usually includes immediate breast reconstruction, may delay therapeutic surgery and subsequent adjuvant treatment [8], as complication rates are higher [9] and the recovery time is increased with bilateral surgery. Delay in treatment (both surgery and adjuvant treatment) may impede the chance of survival from the present cancer [10].…”
Section: Introductionmentioning
confidence: 99%